Ireland : Financial Sector Assessment Program: Technical Note-Asset Management and Financial Stability. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2016)
This Technical Note discusses the findings and recommendations made in the Financial Sector Assessment Program for Ireland in the areas of asset management and financial stability. Most of the potential avenues for domestic financial instability from Irish-domiciled money market funds and investment funds appear to be contained. The potential for destabilizing spillovers from Irish-domiciled money market and investment funds to the domestic economy appears limited. The Central Bank of Ireland has made important progress in addressing long-standing data gaps as they pertain to the asset management industry. A number of initiatives could be helpful in further strengthening industry oversight.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet